Elaboração e análise de indicadores baseados em dados do Sistema Nacional de Pós-Graduação, presentes nos Cadernos de Indicadores Capes - Fioroni, Joyce (2015)
The Post-Graduation system in Brazil is a strategical factor to the socioeconomic and cultural development process of brazilian society, marched by a strict evaluation process and recognition of the Post-Graduation Program (PGP) by the national and international scientific community. The evaluation process stands in this system managed by "Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)" and besides the initiatives of CAPES in endow the country with an efficient database about the situation and evolution of Post-Graduation, there is a underutilization of information by the factors involved on National Post-Graduation System (NPGS) due to form and volume of available data. The general object of this own paper work is the elaboration and review of indicators based on data of NPGS present on Indicators Notebooks of Courses Recommended and Recognized by CAPES, in area of Engineering II. The method used was the exploratory case study and the case unity was the knowledge area from CAPES Engineering II: subarea Materials Engineering and Metallurgic. Collected the data from Notebooks of Bibliographic Production of PGP on area as a documental strategy. Also, was used bibliometrics as technique of information analysis to the elaboration of Bibliometrics Indicators with the support of Software VantagePoint. As results was elaborated and reviewed the indicators of scientific production from PGP: collaboration between the PGP, the evolution of publications, the representativeness of PGP, ranking of periodic and main areas of knowledge. It concludes that the Indicators Notebooks by CAPES consolidate a national source of information, public and with easy access of scientific production national that enables the construction of suitable indicators to decision making process ordering improvement of PGP and the public politics of C&T.